A Convenient Synthesis of Azomethine Imines and Their Cycloaddition Reactions with Some Dipolarophiles - Foroughifar, N.; Mobinikhaledi, A. (Asian Journal of Chemistry, 2012)
Azomethine imines (4a-c) were prepared as 1,3-dipolar structures, from known compounds 5-phenylpyrazolidine-3-one (3) and acetone, thiobenzophenone or benzaldehyde. From the reaction of the 1,3-dipoles (4a-c) with methyl acrylate, ethyl acrylate, phenylisocyanate, N-phenylmalemide, acetylenedicarboxylate and ethyl propiolate products (5-12) were obtained as cyclo-adduct compounds.